会话分析研究 ：以 “Then” 为话语开头单位的 互动会话功能 = Conversation Analysis : a study of the usages and functions of “Then” in Mandarin Conversations - 林勇強 Lim, Yong Kiong (2018)
在日常会话中，说话者通常会以 “所以”、“然后” 和 “因此” 等连接词进行沟通，其目的是为了链接句子前后的话语。然而，在新加坡的语境，说话者一般会使用新加坡式英语（掺杂不同的语言。因此， 本文将以 “then” 为例以探讨它在会话中的运用。本文的研究对象主要是以 “then” 作为话语开头单位。因此，经过田野调查及语料收集，本文发现说话者在进行会话时，会以 “then” 作为连词，有两种现象。其一，说话者以 “then” 来链接自己的话语。其二，听话者与说话者之间的互 动。其他的说话者也能够以 “then” 附加问题的形式以回应之前说话者的话。因此，本文将结合所搜集的语料，以会话分析的角度来探究新加坡华人在什么时候使用 “then” 。其中包含说话者使用 “then” 的方式和 “then” 有几种互动会话功能。这项研究欲理清和归类 “then” 在不同语境中所启动的不同功能以达到理解，并为新加坡式英语的分析研究做出努力。 In daily conversations, a person would normally use conjuctions such as “therefore”, “next” and “so” to begin conversing and to link their speeches. However, in Singapore’s context, speakers would normally converse using ‘Singlish’ (a mixture of different languages). Therefore, this thesis would be using “then” as an example to discuss how it is used in conversation. This thesis aims to show the different usages and functions of “then” while it is being used in casual Mandarin conversations. Therefore, after observation of recorded videos, it could be seen that there are two phenomena whereby a speaker would use “then” as a conjunction. Firstly, speaker would use “then” to link up his or her speeches during conversation. Secondly, the interactions between speaker and listener. Other speakers would also use “then” with a question to ask the previous speaker about what they had said. Therefore, based on first hand corpus, this thesis would be using the “Conversation Analysis” approach to analyze how Singaporean Chinese would use “then”. This would include usages and functions of “then” in different contexts. To have an understanding, this thesis aims to clarify and classify how “then” in different context would have different functions and hopes to contribute to the current research about Singlish.